Zerumbone Suppresses Human Colorectal Cancer Invasion and Metastasis via Modulation of FAk/PI3k/NFκB-uPA Pathway. (2nd January 2019) - Hosseini, Narges; Khoshnazar, Amineh; Saidijam, Massoud; Azizi Jalilian, Farid; Najafi, Rezvan; Mahdavinezhad, Ali; Ezati, Razie; Sotanian, Alireza; Amini, Razieh
Abstract: The current study explored the basic molecular mechanisms of zerumbone (ZER), an herbal compound, in inhibiting the migration and invasion of colorectal cancer (CRC) cells in vitro . Two types of CRC cells, namely HCT-116 and SW48, were treated with various concentrations of ZER (8, 16, and 24 µM) for 24, 48, and 72 h, respectively. In vitro assays were performed to determine alterations in proliferation ability, mRNA expression and protein levels, and migration and invasion potential of CRC cells. An SYBR Green-based quantitative polymerase chain reaction (PCR) was utilized to detect the gene expression of focal adhesion kinase (FAK), nuclear factor (NF)-κB, and urokinase-type plasminogen activator (uPA) followed by the evaluation of the level of proteins by western blotting. Migration and invasion potentials of HCT-116 and SW48 cells treated by ZER were examined using migration and invasion assay kits, respectively. We compared the results of all experiments with control groups, including FAK inhibitor, ZER + FAK inhibitor-treated cells, NF-β inhibitor, ZER + NF-β inhibitor, and untreated cells. The data in the present study suggest that ZER may exert its antimetastatic effects through inhibition of FAk/PI3k/NF-κB-uPA signaling pathway, thereby possibly representing a novel class of FAK inhibitors.